Microvessels in tumor tissue in patients with central nervous system tumors - Agnieszka Nowacka; Maciej Śniegocki; Kamila Woźniak-Dąbrowska; Wojciech Smuczyński (Kazimierz Wielki University, 2021)
Angiogenesis plays an essential role in the development of a tumor. The most preferred histological evaluation method of this process is the determination of microvessel density (MVD) in the biopsy. Numerous studies report the possibility of using various MRI techniques for imaging the network of neoplastic vessels and determining the angiogenesis in them, as well as the subsequent analysis of the obtained images. In this study, a classic MRI imaging with intravenous contrast agent administration was used, and in order to ensure objectification and repeatability, and to eliminate human error that may occur in classic MRI image analysis, an automatic evaluation algorithm was used to determine the degree of angiogenesis, which was then presented in the form of a statistical pixels analysis. The study involved 48 adult patients of both sexes, treated surgically at the Department of Neurosurgery, Nicolaus Copernicus University Collegium Medicum in Bydgoszcz, due to a solid brain tumor. The highest mean density of MVD microvessels in tumor tissue was observed in high-grade gliomas. The high level of MVD expression in tumors of the central nervous system showed a positive correlation with the high degree of tumor malignancy. Based on the conducted research, it was concluded that the determination of the level of MVD expression in the tumor tissue is an additional prognostic factor in neoplasms of the central nervous system. The comparison of the results obtained with the tests performed routinely translates into a more accurate selection of treatment and assessment of the prognosis for survival.